Effect of Role-Play on Students' Speaking Skills in English Instruction: Effect of Role-Play on Students' Speaking Skills in English Instruction - Mona Fitri Gurusinga; Hera Wati Bukit; Maulidina Mutia (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2026)
This study aims to examine the effectiveness of role-play techniques in improving students' speaking skills in English instruction. Speaking is one of the most essential skills in language learning, yet many students face difficulties such as lack of confidence, limited vocabulary, and fear of making mistakes. Role-play is considered an interactive teaching method that encourages students to actively participate in real-life communication situations. This research used a quasi-experimental design involving two groups: an experimental group taught using role-play and a control group taught using conventional methods. The participants were university students enrolled in an English course. Data were collected through pre-test and post-test assessments of speaking performance, focusing on fluency, pronunciation, vocabulary, and grammar. The results showed that students in the experimental group demonstrated significant improvement compared to those in the control group. Role-play activities helped students become more confident, engaged, and motivated in speaking English. Therefore, role-play is an effective strategy to enhance students' speaking skills in English instruction.